Pembangunan Pariwisata di Desa Wisata Penglipuran Melalui Peran Partisipasi Masyarakat, Kewirausahaan Sosial Berkelanjutan dan Inovasi - I Gede Maharta Fujihasa; Ida Ayu Putri Widawati Widawati; Ni Made Eka Mahadewi (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
In this research, which was conducted in Penglipuran Tourism Village, that in Penglipuran Tourism Village as one of the tourist villages visited by many tourists, to find out how to organize a village that is commercialized as a tourist destination and has cultural values, uniqueness and also interesting community habits. tourist interest. However, the economic aspect that has grown through tourist visits who make a visit has not been comparable to being accepted by the community in the midst of community participation, entrepreneurial activities and with the mediation of innovation variables. The sampling technique in this study is a purposive sampling technique, based on an ideal sample calculation, This study uses the Slovin technique with a margin of error of 5% with a total sample of 152 respondents. Methods of data collection using questionnaires and interviews in depth interviews. The data analysis method used a mix method with qualitative interview results used as a support for quantitative data analysis. The research hypothesis was tested using a Structural Equation Model (SEM) approach based on Partial Least Square (PLS). The results showed that all variables had a direct or indirect relationship.